2018
DOI: 10.7554/elife.40750
|View full text |Cite
|
Sign up to set email alerts
|

Altered hippocampal interneuron activity precedes ictal onset

Abstract: Although failure of GABAergic inhibition is a commonly hypothesized mechanism underlying seizure disorders, the series of events that precipitate a rapid shift from healthy to ictal activity remain unclear. Furthermore, the diversity of inhibitory interneuron populations poses a challenge for understanding local circuit interactions during seizure initiation. Using a combined optogenetic and electrophysiological approach, we examined the activity of identified mouse hippocampal interneuron classes during chemo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 94 publications
3
41
0
Order By: Relevance
“…This is further supported by our cell‐attached recordings, and is consistent with a recent report of an acceleration of PV activation ahead of SST and pyramidal cell activation, in two acute, pharmacological in vivo models (Miri et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…This is further supported by our cell‐attached recordings, and is consistent with a recent report of an acceleration of PV activation ahead of SST and pyramidal cell activation, in two acute, pharmacological in vivo models (Miri et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…However, the seemingly paradoxical role of interneurons in seizure must be taken into account when interpreting these findings. While interneurons serve a clear role in restraining seizure propagation, there is also evidence that interneurons are complicit in seizure initiation, potentially serving a causal role 38,43,44,[105][106][107][108] . One hypothesized pathway through which interneuron hyperactivity may contribute to seizure is through the accumulation of chloride in these circuits which can make GABAergic signalling excitatory instead of inhibitory 37,109 , www.nature.com/scientificreports/ a behavior not implemented in our model to preserve mathematical tractability.…”
Section: Discussionmentioning
confidence: 99%
“…By replicating results from the animal literature in which destructive, pharmacological, or optogenetic manipulations have been performed. Previous studies in animal models have shown that neuronal firing is less precise when feed-forward inhibition is altered (Foffani et al, 2007;Ibarz et al, 2010;Miri et al, 2018;Trevelyan, 2009). This lack of action potential timing reliability has been related to several cellular processes.…”
Section: Discussionmentioning
confidence: 99%